Expediting specialist referral for patients with suspected lung cancer through standardization of radiologist reporting. Issue 4 (28th July 2022) - Golemiec, Breanne; Mullin, Monica L.L.; Linton, Sophia; Howard, Thomas; Dhillon, Gurmohan Rob; DaBreo, Dominique; Parker, Christopher M.; Digby, Geneviève C.
Abstract: RATIONALE: Lung cancer (LC) diagnostic pathways are often initiated following suspicious clinical and radiologic findings. We identified delays from first thoracic imaging suspicious for LC to specialist evaluation in a rapid assessment clinic [Lung Diagnostic Assessment Program (LDAP)]. OBJECTIVES: We evaluate the impact of a quality improvement initiative consisting of standardized Computed Tomography (CT) reporting on timeliness of LC diagnostic pathways. METHODS: Retrospective chart review of LDAP-referred patients established baseline data (January – December 2018). Improvement initiatives included (i) implementation of standardized LDAP referral recommendations at an academic center for patients with suspected LC by thoracic imaging (January 2019), and (ii) spread of standardized reporting to 3 community hospitals (March 2019). Prospective chart review (January - September 2019) evaluated for improvement. Data include dates of CT chest, LDAP referral/assessment and specific phrasing of radiology reports. Continuous data are reported as medians, categorical data as percentages; Mann-Whitney U and chi-squared tests assess for significance. MEASUREMENTS AND MAIN RESULTS: We reviewed 1, 244 LDAP referrals (697 baseline; 547 post-standardization). Patients with a radiologist recommendation for LDAP referral had faster times from CT to referral (median [75 th, 90 th percentile]) (5[9, 15] vs. 6[16, 33] days) and specialist assessment (20[27, 35] vs. 22[33, 50] days). Following standardization, the percentage of LDAP-referred patients with a radiologist recommendation for referral increased (29.2% to 48.3%; P < .001), significant for the academic center (50.2% to 61.8%; P = .006) and community hospitals (12.1% to 35.3%; P < .001). CONCLUSIONS: Standardized radiologist reporting and specialist referral recommendations for patients with imaging suspicious for LC leads to faster patient referral and assessment.